Sosialisasi Dampak Penggunaan TikTok Bagi Siswa SMA YPK Oikumene Manokwari - Yammes J.Batkunde; Yuliana Sangka; Jennis Tonapa; Engelberth Worabai; Mardewi; Joice Pangulimang; Risma Petrus; Irmawati Leppang; Nirmala; Aulia Dwi Syahputri Moreira (AMMA : Jurnal Pengabdian Masyarakat, 2025)
TikTok is a platform that is widely loved by teenagers, especially among high school students. However, excessive and unsupervised use of TikTok can have negative impacts such as decreased student concentration, TikTok addiction, and exposure to age-inappropriate content. YPK Oikumene Manokwari High School became the object of Community Service (PKM) because many parents and educators are still unfamiliar with how TikTok works, making it difficult to provide guidance or supervision to students. This community service activity was carried out to provide an understanding of the positive and negative impacts of TikTok.